Disadvantaged Youth in Southern Scotland Experience Greater Barriers to Information Access Resulting from Poor Technology Skills, Information Literacy, and Social Structures and Norms - Coates, Heather L (Evidence Based Library and Information Practice, 2016)
A Review of: Buchanan, S., & Tuckerman, L. (2016). The information behaviours of disadvantaged and disengaged adolescents. Journal of Documentation, 72(3), 527-548. http://dx.doi.org/10.1108/JD-05-2015-0060 Objective – To describe the information behaviours of adolescents living in disadvantaged and disengaged circumstances in relation to social integration and self-efficacy. Design – Mixed methods design using observation, semi-structured interviews, and focus groups. Setting – Public agencies offering drop-in support services for employment and training at three locations in South Ayrshire, Scotland. Subjects – Adolescents aged 16-20 not in education, employment, or training (NEET status) seeking public agency support services in South Ayrshire, Scotland; and public agency support workers. Methods – The South Ayrshire region was identified using the Scottish Index of Multiple Deprivation (2012) and selected because nearly 20% of the region fell into the most deprived decile. Participants were recruited using purposive sampling of NEET youth attending drop-in support groups. Over a period of 4 weeks, the 36 NEET youth attending these sessions were observed regarding their information behaviours, social interactions, and experiences with support workers. Following observation, the investigator used the critical incident technique during interviews to discuss real life scenarios and needs with 15 participants. One focus group of four interview participants was held to explore how groups discuss information behaviours. An information resource sorting activity was used as a discussion prompt. To gain further insight into the information needs, sources used, and barriers experienced by the adolescents who sought support, six support workers were also interviewed. These data were analyzed using iterative deductive coding and thematic analysis. Main Results – Internet usage of participants is similar to general population peers, with general browsing, social networking, and music and gaming usage as the most popular activities. Information needs included employment, education, and training such as finding appropriate job vacancies, identifying employer addresses and contact details, and accessing public transportation schedules. Other personal needs such as financial, health, and housing were identified. Some of these information needs were unmet, which could have implications for their wellbeing. Approximately one third of the interview participants described challenges identifying or meeting needs. Teens frequently rely on people as sources of information, preferring face-to-face interactions. They turn to family, friends, and support workers for information as important members of their social network who listen and “usually have the answer.” Other frequently used sources include the Internet and television news. A third of the interview participants described scenarios in which they used multiple sources – the Internet, family and friends, books and leaflets, and local youth clubs and health clinics. A majority of interview participants (73%) did not use the public library because they were not interested (“I don’t read books”) or thought there was nothing there for them. Of the four who used public libraries, none considered themselves regular users. Focus group participants rated support workers and television news as having high credibility, friends and family as having low credibility, and the Internet as having medium credibility. The information seeking behaviours of NEET teens are often passive and non-motivated, with abandonment and incompletion occurring frequently. Many observation participants appeared visibly withdrawn and were reluctant or unable to engage in discussion with support workers. Throughout the study, participants demonstrated an unwillingness to engage in lengthy discussions. Support workers noted that attendees rely on them to find the information, evaluate it, and give the teens advice about what to do next. Participants exhibited bonding social capital with family and friends, though evidence for bridging social capital was found only with support workers. These adolescents appear to be relatively isolated and have more inward-facing social capital, which puts them at risk for social exclusion. Though nearly two thirds of interview participants reported no barriers to finding information, evidence from observations and support worker interviews suggest that deficits in technology and literacy skills are substantial. Despite assistance from support workers, NEET youth often abandoned tasks before completing them due to literacy and technological barriers. Support workers described a variety of barriers to meeting information needs: home life, isolation, literacy and access, institutional regulations, motivation, lack of confidence, and poor social skills. Common circumstances relating to motivation are familial unemployment, substance abuse issues, and inability to focus. Conclusion – NEET youth faced increased access and behavioural barriers beyond those of typical adolescents. Access barriers are influenced by technology and literacy skills deficits, while behavioural barriers are influenced by social structures. Considering the range of personal needs expressed to support workers in combination with pervasive barriers to information, further study of everyday information needs is warranted. Public and third sector (e.g., typically voluntary and community organizations, associations, etc.) agencies should make remedial literacy education a priority. Since the perception of public libraries is poor, librarians should collaborate with third sector agencies to develop tailored outreach and services to build sustained relationships with these disengaged adolescents. Generally, these adolescents exhibit self-protective behaviours (e.g., deception, risk-taking, secrecy) in seeking out information as well as situation relevance of information sources and inward-facing social networks, all of which suggest they live in an impoverished information environment.